Students’ Adoption of Wearable Financial Devices: A Survey-Based Analysis - Hao, Huang; Shuo, Wang; Wenjie, Xu; Jiayi, Wang; Amir, Aliana Shazma; Isa, Evawaynie Valquis Md. (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2025)
This study investigates students’ adoption and perceptions of wearable financial devices, such as smartwatches and fitness trackers with payment capabilities. A survey‐based descriptive approach was employed with ten university students to assess their views on usefulness, ease of use, trust, security, and behavioral impact. Descriptive statistics revealed generally positive attitudes toward wearable financial devices. Respondents expressed strong trust in data privacy and were likely to recommend such devices to peers, although perceptions of convenience and usage frequency were moderate. The findings also indicate that wearable payments had limited influence on saving habits and financial awareness. Peer influence nevertheless emerged as an important factor driving adoption among students.These results support the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) in the wearable payments context. This study contributes to FinTech and wearable technology research by showing how these devices are now embedded into students’ routines and suggests design improvements and educational strategies to strengthen their financial utility.